2019
DOI: 10.1039/c9pp00410f
|View full text |Cite
|
Sign up to set email alerts
|

Blue fluorescence from N,O-coordinated BF2 complexes having aromatic chromophores in solution and the solid state

Abstract: N,O-Coordinated BF2 complexes (Ar@HCs) having aromatic (Ar) and heterocycle (HC) moieties were prepared, and their photophysical properties were investigated in solution and the solid state along with their crystal structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…24 Combining the amide bond linkage moiety of the 2-position in the pyridine skeleton, the compound containing pyridine unit could act as a precursor of difluoroboron compounds. 25 As previously reported, we found that pyridine-based difluoroboron compound with the TPA group at the end of amide bond linkage moiety could be applied in the field of inkless writing. 26 If the TPA group was located at the 4-position of pyridine skeleton, the synthesized compound displayed also had excellent luminescent performance.…”
Section: Introductionsupporting
confidence: 53%
“…24 Combining the amide bond linkage moiety of the 2-position in the pyridine skeleton, the compound containing pyridine unit could act as a precursor of difluoroboron compounds. 25 As previously reported, we found that pyridine-based difluoroboron compound with the TPA group at the end of amide bond linkage moiety could be applied in the field of inkless writing. 26 If the TPA group was located at the 4-position of pyridine skeleton, the synthesized compound displayed also had excellent luminescent performance.…”
Section: Introductionsupporting
confidence: 53%
“…147 In this category, Okamoto and co-workers reported a methodology to prepare a family of N,O-coordinated BF 2 complexes (45a−45g) with head-to-tail stackings as the primary arrangements observed on their X-ray structures. 148 In addition, simple B−N coordinated compounds also display DSE properties. Feng and co-workers reported compound 46 with a low quantum yield in solution (Φ F = 3%) but moderate solid state (Φ F = 54%).…”
Section: Classification Of Dual-state Emission Compounds: Frequent Mo...mentioning
confidence: 99%
“…The D–A complexes 44a – 44d (Scheme ) reported by Chujo and co-workers also display DSE properties with quantum yields ranging from Φ F = 17% to Φ F = 80% in solution and Φ F = 25% to Φ F = 81% in the solid state . In this category, Okamoto and co-workers reported a methodology to prepare a family of N , O -coordinated BF 2 complexes ( 45a – 45g ) with head-to-tail stackings as the primary arrangements observed on their X-ray structures …”
Section: Classification Of Dual-state Emission Compounds: Frequent Mo...mentioning
confidence: 99%